The Relationship among Technology Utilization, Obedience to Law and Smoking Culture In Community with Smoking Behavior in Male Adolescents in Semarang Indonesia - Retno Indarwati1 , Kristiawati Woespinto2 , Inas Husnun Hanifah2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Smoking behavior in adolescent is still a problem recently. The number continue to increase.This study purpose was to investigate the connectedness of technology utilization, obedience to law, andsmoking culture in community with smoking behavior in adolescent in Semarang.Method: This study used cross sectional method. The sample was 104 adolescents with range age 15-17 years old. The sample was chosen using purposive sampling. Data collection using a questionnaire.Four aspects namely demographic data, technology utilization, obedience to law, and smoking culture incommunity were measured. Those variables the compared to smoking behavior of adolescents. The datathen analyzed with Spearman’s Rho (? = 0.05).Conlusion: This study found that technology has no significant correlation with smoking behavior (r=0.017;p=0.864). There is significant correlation between obedience to law (r=0.284; p=0.003), and smokingculture in community (r=0.251; p=0.014) with smoking behavior in adolescences. It is necessary for effortsfrom various parties to overcome smoking behavior in adolescents such as the need for socialization in thecommunity to participate in preventing adolescents who smoke in their environment.